2019
DOI: 10.3389/fcimb.2019.00338
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Human Skin Lesions Identifies Tryptophan-2,3-Deoxygenase as a Restriction Factor for Cutaneous Leishmania

Abstract: Disease manifestation after infection with cutaneous Leishmania species is the result of a complex interplay of diverse factors, including the immune status of the host, the infecting parasite species, or the parasite load at the lesion site. Understanding how these factors impact on the pathology of cutaneous leishmaniasis (CL) may provide new targets to manage the infection and improve clinical outcome. We quantified the relative expression of 170 genes involved in a diverse range of biological processes, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…The administration of pentavalent antimonial sodium stibogluconate (20 mg/kg for 20 days) in infected macaques, reduced the lesion severity and accelerated healing, which was associated with the modulation in the expression of hundred genes in the skin biopsies from the lesion site [63] . These findings are in agreement with data from human biopsies, which demonstrated that treatment failure was linked to the excessive activation of the cytolytic pathway activated during infection [64] , [65] . Additional studies in macaques could also address the role of tryptophan-2,3-deoxygenase (TDO), that has recently been described to inhibit parasite burden in human lesions and cultured macrophages [65] .…”
Section: Introductionsupporting
confidence: 92%
“…The administration of pentavalent antimonial sodium stibogluconate (20 mg/kg for 20 days) in infected macaques, reduced the lesion severity and accelerated healing, which was associated with the modulation in the expression of hundred genes in the skin biopsies from the lesion site [63] . These findings are in agreement with data from human biopsies, which demonstrated that treatment failure was linked to the excessive activation of the cytolytic pathway activated during infection [64] , [65] . Additional studies in macaques could also address the role of tryptophan-2,3-deoxygenase (TDO), that has recently been described to inhibit parasite burden in human lesions and cultured macrophages [65] .…”
Section: Introductionsupporting
confidence: 92%
“…Macrophages also utilize tryptophan for NAD + biosynthesis, with tryptophan 2,3‐dioxygenase (TDO) catalyzing the first step. Although TDO expression is not induced by IFNγ, TDO levels are negatively correlated with parasite load in L. major cutaneous lesions and TDO inhibition in ex vivo infected macrophages promotes parasite growth 49 . Whether indoleamine‐2,3‐dioxygenase and TDO act synergistically or separately to restrict Leishmania growth needs further investigation.…”
Section: Impact Of Macrophage Metabolism On Intracellular Leishmania mentioning
confidence: 99%
“…IFNc-activated M1 macrophages upregulate expression of indoleamine-2,3-dioxygenase and the conversion of tryptophan to kynurenine metabolites, reducing the availability of tryptophan to amastigotes. 49 Indoleamine-2,3-dioxygenase is highly expressed in cutaneous Leishmania lesions, although the impact of indoleamine-2,3-dioxygenase 1 expression on parasite burden remains poorly defined. Macrophages also utilize tryptophan for NAD + biosynthesis, with tryptophan 2,3-dioxygenase (TDO) catalyzing the first step.…”
Section: Host Tryptophan Metabolismmentioning
confidence: 99%
See 2 more Smart Citations